Fraud Triangle Analysis And Gone Theory In The Management Strategy Of Self-Managed Special Allocation Fund In Education Sector - Saut Saut; Wanapri Pangaribuan; Jemeria Pangaribuan (UNIVED Press, 2025)
This study aims to analyse the application of the Fraud Triangle, which includes pressure, opportunity, and rationalisation, as well as the GONE Theory, which involves greed, opportunity, need, and exposure, in the self-management Special Allocation Fund (DAK) management strategy in the education sector. The results show that pressure on fund managers often comes from demands to meet unrealistic physical or non-physical development targets, while opportunities arise from weak supervisory systems, lack of transparency and inadequate internal control mechanisms. Rationalisation is found in the form of justifying fraudulent actions with certain reasons, such as urgent needs or for the smooth running of the program. In the GONE Theory perspective, greed is the main driver of misuse of funds, while necessity and weak risk exposure increase the probability of violations. There are several things that can be done by educational institutions and students themselves to minimise student fraud behaviour, first from the aspect of pressure which is the main aspect that encourages someone to commit fraud. The pressure aspect comes from a person's psychology, so the way to overcome it is to provide positive directions, and provide spiritual and emotional strengthening to students. Transparent, accountable DAK management supported by strong supervision is essential to ensure that the main objectives of using funds are achieved, namely improving the quality of education and equitable development.